Advancing Grid-Forming Inverter Technology: Comprehensive PQ Capability and Performance Analysis - Md Nurunnabi; Shuhui Li; Himadry Shekhar Das (IEEE Access)
This paper presents a performance analysis of grid-forming (GFM) inverter technology, which is essential to ensure stable and reliable operation of power systems with high penetration of inverter-based resources (IBRs). Recognizing that IBR operational constraints are distinct from those of synchronous generators, this study develops advanced PQ capability models and algorithmic frameworks that accurately characterize GFM inverter operational constraints across various coupling filter configurations (L, LC, and LCL). Electromagnetic transient (EMT) simulations show that the Enhanced Voltage Regulation (EVR) and Controlled Proportional-Integral Droop (CPID) strategies proposed in this paper improve voltage and frequency stability under dynamic loading and fault conditions, outperforming conventional droop methods. Real-time hardware validation confirms the robustness of the proposed approaches and their effectiveness in suppressing harmonics and recovering from faults. Key contributions include the derivation of practical PQ capability boundaries under realistic constraints, identification of superior control strategies for robust power quality (PQ), and successful GFM and grid-following (GFL) integration in parallel operations. These findings provide actionable insights for optimizing GFM inverter design and ensuring IEEE 1547 compliance in low-inertia grids.